Evaluación de los contaminantes criterio (material particulado) en las localidades de la ciudad de Bogotá que presentaron mayor contaminación atmosférica durante los dos primeros trimestres del año 2020. (2022)
The present document aims to evaluate the variability in a given period of time of the amount of PM10 and PM2.5 particles in the city of Bogotá from the data of the RMCAB monitoring stations. The first two quarters of 2020 were chosen as a temporary space, taking into account that they cover pre-pandemic periods, the beginning of confinement and the months of greatest restriction for mobility due to SARS COV 2 Covid 19.